Effect of midwife competence training in primary healthcare facilities on obstetric risk early detection - Ai Nur Zannah; Yuningsih Yuningsih; Asri Iman Sari; Eka Afdi Septiyono (PAGEPress Publications, 2024)
Early detection of obstetric risk is the main competence of midwives to anticipate the mother's inability to adapt during pregnancy. The early detection competence of midwives determines the success of obstetric risk management, preventing pain and even death of mothers and babies. This study aimed to analyze the effect of obstetric risk early detection training on improving the competence of midwives in basic health care facilities. The study employed a quasi-experimental pre-posttest design with a control group. The samples were selected based on inclusion criteria, encompassing independent practice midwives and public health center midwives. The study comprised 27 midwives in the treatment group and 27 in the control group. The determination of and control groups was conducted through simple random sampling. Data analysis involved the use of Mann-Whitney and T-tests. The results indicated a significant difference in the increase in midwife competence within the treatment group post-training (p-value <0.001), with a notable improvement of 34.5%, compared to a 14.53% rise in midwife competence within the control group after reading the training module. Although a slight decrease in competence was observed after 2-4 weeks of training, the posttest values remained considerably higher than the pretest values. These findings underscore the impact of training on midwife competence, emphasizing the continual need for midwives to enhance their skills to elevate the health outcomes for the mothers and children under their care.